TRENDS, PATTERNS, AND DETERMINANTS OF ROAD TRAFFIC ACCIDENTS IN NORTH-WEST NIGERIA: A LONGITUDINAL ANALYSIS (2016–2024) - Tanko, N. A.; Onyishi, I. L.; Musa, S. A. (FUDMA Journal of Sciences, 2025)
Road traffic accidents (RTAs) represent a critical public health challenge in Nigeria, with the North-West region experiencing a disproportionate burden due to its role as a major commercial corridor. This study provides a comprehensive statistical analysis of RTA trends, patterns, and severity across the seven states of North-West Nigeria from 2016 to 2024. Methods utilizing official data from the Federal Road Safety Corps, we employed descriptive statistics, two-factor analysis of variance, and post-hoc tests to analyze accident frequency, injuries, fatalities, and people involved. We computed casualty severity indices and fatality rates to assess accident severity across states. Results from the analysis revealed a dramatic surge in RTAs in 2024, with Kaduna State bearing the highest burden in absolute terms (7,804 crashes, 4,348 deaths). However, Katsina and Zamfara recorded the highest fatality rates (0.64), indicating more deadly crashes. A significant interaction effect (p<0.001) between states and crash metrics confirmed distinct state-specific accident profiles. The casualty severity index exceeded 50% across all states, peaking in Sokoto at 68%. Conclusion North-West Nigeria faces an escalating RTA crisis with substantial variations in accident patterns across states. The findings underscore the necessity for targeted, state-specific interventions rather than uniform regional approaches. Recommendations include enhanced data collection, infrastructure improvements, and coordinated multi-agency responses to address this public health emergency.